PERTUMBUHAN EKONOMI REGIONAL DI INDONESIA: PERAN INFRASTRUKTUR, MODAL MANUSIA DAN KETERBUKAAN PERDAGANGAN - Kustanto, Andi (Buletin Studi Ekonomi, 2020)
This study discusses the analysis of the impact of infrastructure development, human capital and trade openness on regional economic growth in Indonesia using the panel data method. The model was built based on the Solow growth model using road infrastructure, electricity infrastructure, health infrastructure, life expectancy, mean years of schooling and trade openness in 34 provinces in Indonesia. Estimation results obtained from this study using the fixed effects model indicate that regional economic growth in Indonesia is influenced by electricity infrastructure, health infrastructure, mean years of schooling, life expectancy, and trade openness. Whereas road infrastructure has a negative and not significant effect on regional economic growth in Indonesia. Life expectancy has the biggest impact on regional economic growth followed by mean years of schooling, health infrastructure, electricity infrastructure, and trade openness.